2015
DOI: 10.1115/1.4028198
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Simulation of Localized Electrochemical Deposition for Maskless Electrochemical Additive Manufacturing

Abstract: Localized electrodeposition (LED) was explored as an additive manufacturing technique with high control over process parameters and output geometry. The effect of variation o f process parameters and changing boundary conditions during the deposition process on the output geometry was observed through simulation and experimentation. Trends were found between specific process parameters and output geometries in the simula tions; trends varied between linear and nonlinear, and certain process parameters such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Future work is required to optimize the techniques, or try a new technique entirely. Additionally, the alteration of tool size needs to be explored experimentally; this has been shown in simulations to have an impact on the electrical behavior and deposition geometry (Brant et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Future work is required to optimize the techniques, or try a new technique entirely. Additionally, the alteration of tool size needs to be explored experimentally; this has been shown in simulations to have an impact on the electrical behavior and deposition geometry (Brant et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…An in-house electrochemical setup developed in prior work (Brant, Sundaram, & Kamaraj, 2015;Sundaram, Kamaraj, & Kumar, 2015) was used to perform micro additive manufacturing. The setup is illustrated in Figure 1(a).…”
Section: Physical Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…If numerical models are able to handle technological, physical, and geometrical constrains, design guidelines can be adopted by coupling the optimisation tool to decision making paradigms. Some studies show that AM process simulation is possible [125,126] but the ultimate goal would be to bridge such realistic tools with the optimisation paradigm. Recent works prove unfortunately that we are far from such ideal situation [127].…”
Section: Optimisation In Additive Manufacturingmentioning
confidence: 99%
“…Very few studies have reported the use of pulse power for localized electrochemical deposition. A finite element based study of the localized deposition lists the effects of voltage, concentration of electrolyte, and interelectrode gap during the deposition [36]. Lower duty cycles result in lesser pores and a smoother finish.…”
Section: Literature Reviewmentioning
confidence: 99%